Study of Management of anemia in Chronic Kidney Disease Patients - Mathew, Meby Susan; Keerthi, Nama Ravi Sneha; Meera, Neelathahalli Kasturirangan (Indian Journal of Pharmacy Practice)
Background: Anemia is the common comorbidity in patients with chronic kidney disease (CKD). Clinical studies have shown that erythropoietin-stimulating agents decrease the need for transfusions and improve the quality of life. Objectives: The objectives were to assess the management of anemia, provide counseling and to create awareness among the patients using patient information leaflets. Methodology: A prospective, hospital based study was conducted for a period of nine months on 82 dialysis patients suffering from anemia in chronic renal failure condition. A written informed consent was obtained from all the patients before inclusion in the study. Patient demographics, laboratory data and treatment chart were reviewed. Patient information leaflets, diet chart were given along with counseling at base line and during follow ups. The study results were analyzed by descriptive statistical analysis. Student t test was used to find significance of study parameters at base line and follow up. Results: The mean hemoglobin levels showed an increase in patients with epoetin therapy. The parameters like serum ferritin, serum iron, TSAT and serum folate showed an increase in both patients who received epoetin as well as those on oral iron therapy. Conclusion: It can be concluded that early detection and treatment of anemia with effective counseling from clinical pharmacist benefits CKD patients.
Keywords: Chronic kidney disease; Erythropoietin; Hemodialysis; Anemia